2022
DOI: 10.1111/jace.18769
|View full text |Cite
|
Sign up to set email alerts
|

Steam oxidation and microstructural evolution of rare earth silicate environmental barrier coatings

Abstract: A primary failure mode for environmental barrier coatings (EBCs) on SiC ceramic matrix composites (CMCs) is the oxidation of the intermediate Si‐bond coating, where the formation of SiO2 at the bond coating–EBC interface results in debonding and spallation. This work compares the microstructure evolution and steam oxidation kinetics of the Si‐bond coating beneath yttrium/ytterbium disilicate ((Y/Yb)DS) and ytterbium disilicate/monosilicate (YbDS/YbMS) EBCs to better understand the impact of EBC composition on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Further, it is known that SiO 2 undergoes a phase transformation upon cooling around 250 • C which results in cracking. [29][30][31][32] Fast removal of the C-rich phase encouraged additional cracking of the residual SiO 2 phase to create more oxidant pathways for subsequent exposures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, it is known that SiO 2 undergoes a phase transformation upon cooling around 250 • C which results in cracking. [29][30][31][32] Fast removal of the C-rich phase encouraged additional cracking of the residual SiO 2 phase to create more oxidant pathways for subsequent exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Complex ceramics with low oxidant diffusivities remains an active area of research, yet many environmental barrier coating candidates are currently available. 10,32,37 Standard deposition methods for high-temperature ceramic coatings focus on plasma spray processes that are primarily line-of-sight. 38 Slurry-type coating deposition processes may be an option most readily available for complex geometries desired with additively manufactured SiC-base composites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The remarkable physicochemical properties of rare earth elements have made them 'industrial gold.' Their unique physical and chemical properties have widespread applications in various fields, such as military, electronics, metallurgy, optics, agriculture, chemicals, and medicine [1][2][3][4][5]. Recent research has shown that surface treatment can introduce the right amount of reactive yttrium (Y) content into nitride hard films, thereby improving their hardness, adsorption capacity, and resistance to high-temperature oxidation.…”
Section: Introductionmentioning
confidence: 99%